A pilot study using residual newborn dried blood spots to assess the potential role of cytomegalovirus and Toxoplasma gondii in the etiology of congenital hydrocephalus. Issue 7 (28th May 2013) - Simeone, Regina M.; Rasmussen, Sonja A.; Mei, Joanne V.; Dollard, Sheila C.; Frias, Jaime L.; Shaw, Gary M.; Canfield, Mark A.; Meyer, Robert E.; Jones, Jeffrey L.; Lorey, Fred; Honein, Margaret A.
Abstract Background Congenital hydrocephalus is a condition characterized by accumulation of cerebrospinal fluid in the ventricles of the brain. Prenatal infections are risk factors for some birth defects. This pilot study investigated whether residual dried blood spots (DBS) could be used to assess infections as risk factors for birth defects by examining the associations between prenatal infection with Toxoplasma gondii (T. gondii) or cytomegalovirus (CMV) with congenital hydrocephalus. Methods Case‐infants with hydrocephalus (N = 410) were identified among live‐born infants using birth defects surveillance systems in California, North Carolina, and Texas. Control‐infants without birth defects were randomly selected from the same geographic areas and time periods as case‐infants (N = 448). We tested residual DBS from case‐ and control‐infants for T. gondii immunoglobulin M and CMV DNA. When possible, we calculated crude odds ratios (cORs) and confidence intervals (CIs). Results Evidence for prenatal T. gondii infection was more common among case‐infants (1.2%) than control‐infants (0%; p = 0.11), and evidence for prenatal CMV infection was higher among case‐infants (1.5%) than control‐infants (0.7%; cOR: 2.3; 95% CI: 0.48, 13.99). Conclusions Prenatal infections with T. gondii and CMV occurred more often among infants with congenital hydrocephalus than control‐infants, although differences were not statistically significant. This pilot study highlighted some challenges in using DBS to examine associations between certain infections and birth defects, particularly related to reduced sensitivity and specimen storage conditions. Further study with increased numbers of specimens and higher quality specimens should be considered to understand better the contribution of these infections to the occurrence of congenital hydrocephalus. Birth Defects Research (Part A) 97:431–436, 2013. © 2013 Wiley Periodicals, Inc.